Pre-service teachers' desire to control bias: Implications for the endorsement of culturally affirming classroom practices. (April 2022) - Kumar, Revathy; Gray, DeLeon L.; Kaplan Toren, Nurit
Abstract: The study integrates social-psychological and educational research to examine the relations between preservice teachers' race-related perceptions of Black students and the instructional approaches they endorse. Based on survey and race Implicit Association Test data from preservice teachers (N = 258; White = 82%) in the United States, we predicted that the association between motivation to be unprejudiced and motivation to appear unprejudiced would predict endorsement of culturally and motivationally supportive instructional practices via implicit and explicit biases about Black students. Path analyses revealed significant mediated associations among motivation to be unprejudiced and endorsed instructional approaches and practices via explicit bias, contingent on the motivation to appear unprejudiced. Furthermore, it is troubling to note that White preservice teachers, in contrast to their ethnic minority counterparts, displayed significant implicit preference for White over Black students. Implications of these findings for preparing a culturally responsive and motivational supportive teaching task-force are discussed. Highlights: It is vital to be motivated to be genuinely unprejudiced to overcome racial bias. Explicit bias varies by the levels of motivations to be and to appear prejudiced. White preservice-teachers displayed implicit bias toward Black students. Motivation to be/appear unprejudiced is related to proposed teaching practices. It is important to recruit ethnic minority students in teacher education programs.